Effects of organic acid treated legume forages on in vitro degradability values - Palangi, V; Macit, M; Kilic, U (Journal of the Hellenic Veterinary Medical Society, 2023)
In this context, we aimed to investigate the effects of varying levels of Fumaric Acid (Fu), Malic Acid (Ma), Formic Acid (Fo), and their combinations on in-vitro degradability parameters, organic matter digestibility (OMD), metabolizable energy (ME) and net energy lactation (NEL) of alfalfa (Medicago polymorphia), white clover (Trifolium repens) and hairy vetch (Vicia villosa). Obtained data were analyzed as a completely randomized 3×8 factorial design, with GLM using SAS 9.4. The effects of legume forages and their interacion with organic acid were significant on ME, NEL and OMD values (p<0.05, p<0.01). in such a way that fumaric acid was led to an increase NEL. All of the parameters, except ME and OMD, were affected by organic acids (p<0.01). To conclude, utilization of organic acids could increase NEL, reduce the fermentation of insoluble fraction (b) and potential extent of gas production (a+b) from ruminants and reduce rapidly soluble fraction (a) (malic acid treatment only).